Iklan
Iklan
Pengguna Brainly Pengguna Brainly

 \frac{3}{4}  +  \frac{1}{2}  -  \frac{2}{ 3}

 =  \frac{5}{4}  -  \frac{2}{3}

 =  \frac{5 \times 3}{12}  -  \frac{2 \times 4}{12}

 =  \frac{15}{12}  -  \frac{8}{12}

 =  \frac{(15 - 8)}{12}

 =  \frac{7}{12}

Iklan
Iklan

Jawaban:

\frac{3}{4}+\frac{1}{2}-\frac{2}{3} = \frac{3 \times 3}{4 \times 3}+\frac{1 \times 6}{2 \times 6}-\frac{2 \times 4}{3 \times 4} =\frac{9}{12}+\frac{6}{12} -  \frac{8}{12} =\frac{7}{12}

Penjelasan dengan langkah-langkah:

SEMOGA MEMBANTU

Iklan
Iklan